Image Encryption Based on Partitioning and Rearranged Pixels Position - Jamila H. Al-A’meri; Salah T. Allaw; May M. Abbas (QALAAI ZANIST JOURNAL, 2021)
Protect important information transmitted via the channels of communication it’s one of the important area. Today, especially with the increasing use of the Internet in the process of transferring this information you had to find ways to protect this information for fear of being captured by unauthorized people to look at it. The image and what it contains is one of the fore mentioned knowledge that should be protected. In our paper a new method is suggested for protecting information of colored image by rearranging the distribution of image pixels. This way depends on the image partition into four equal parts where each data stored in a 1-D array, then the data of these parts are re-arranged through random numbers generated by using LFSR to produce a new (2-D) array combines the data of the four-part. Finally, the new array is converted to another color space YCbCR and the result will be representing the stego image.